2014
DOI: 10.1007/s00404-014-3388-0
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient versus inpatient intravaginal misoprostol for the treatment of first trimester incomplete miscarriage: a randomised controlled trial

Abstract: Medical evacuation using intra-vaginal misoprostol 800 mcg eight hourly for a maximum of three doses in an outpatient setting is as effective as in inpatient setting with tolerable side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A total of 114 RCTs were included in the review . The PRISMA flow chart in Figure S1 shows study selection.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 114 RCTs were included in the review . The PRISMA flow chart in Figure S1 shows study selection.…”
Section: Resultsmentioning
confidence: 99%
“…In the usual practice, some professionals are concerned about the occurrence of infection when surgical treatment is not chosen. In 2006, the Miscarriage Treatment (MIST) Trial 31 randomized 1,200 patients diagnosed with a first-trimester miscarriage to be treated surgically, medically, or expectantly. The results showed no difference in the incidence of infection within 14 days of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the side effects and complications were similar between the two groups. 9 The higher success rate may be a consequence of the higher dose of misoprostol (a total of 2,400 µg) administered within a shorter interval.…”
Section: Discussionmentioning
confidence: 99%
“…4 Over the years, many studies observed the efficacy and acceptance of misoprostol as a treatment option for incomplete and delayed miscarriage, 3,5,6 and as an option in outpatient management protocols, with success rates ranging from 77.3% to 92.7%. 5,[7][8][9] The efficacy of the medical treatment with prostaglandins depends on both the dose and route of administration. Hence, the vaginal administration of misoprostol seems to be more effective than the oral administration, and has less side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation